Enhancing Technology-Based Learning through Wordwall Application: A Case Study at SMAN 1 Ampek Angkek - Mukhti, Tessy Octavia; Fitri, Fadhilah; Sari, Widia Kemala (Pelita Eksakta, 2025)
The explosive growth of technology necessitates educators staying current with the latest innovations, especially for technology-based learning in the sciences. However, at SMA Negeri 1 Ampek Angkek, it was discovered that several teachers have varying levels of technological proficiency, face resource constraints, and struggle to develop interactive learning materials. As a result, students often lose interest in learning. To solve this problem, a training session on using the Wordwall application, a web-based educational tool that includes interactive tools like puzzles, flashcards, and quizzes, was held. The workshop aimed to help teachers create more interactive and interesting teaching methods, as well as improve their ability to use educational technology. As a result, the training session improved the quality of teaching at SMA Negeri 1 Ampek Angkek, making the classroom atmosphere more dynamic and interesting for students.